Economic and Socio-Cultural Relations between Indonesia and Taiwan: An Indonesian Perspective, 1990-2012 - Kabinawa, Luh Nyoman Ratih Wagiswari (JAS (Journal of ASEAN Studies), 2013)
This paper analyzes the puzzle why did Indonesia maintain durable economic and socio-cultural relations with Taiwan? In order to answer that question, this paper argues that due to the Indonesian people as promoter of ideas lead interactions with Taiwan, Indonesia is able to maintain its durable economic and socio-cultural relations with Taiwan despite under the absence of diplomatic relations. People-to-people interaction builds three kinds of interactions between Indonesia and Taiwan on the issue of economic and socio-cultural: unofficial interaction, semi-official interaction, and official interaction. This paper employs Indonesian perspective approach that stressed on the pattern of relations that stem from people-to-people interactions between Indonesia and Taiwan. Thus, the paper aims to fill the gap in the literature on Taiwan and Indonesia relations that mostly focus on analysis of economic diplomacy, interest (Leifer 2001; Ku 1995, Leong 1995, Lee 1990, Klintworth 1995, Rich 2009), shifting on international order (Ku;1998), and the PRC’s factor on Indonesia and Taiwan relations (Ku 2002; Irawan 2006).